Evaluation of sorption moistening in research of moisture-caused deformations of building materials - Miniotaitė, Rūta; Stankevičius, Vytautas (Journal of Civil Engineering and Management, 2003)
Investigation methods described in literature and standards do not evaluate the influence of sorption moisture upon moisture-caused deformations of building materials. Therefore, the usual deformations measuring methods had to be amended by measuring moisture deformations in various models and by setting sorption moisture. The improved methods was applied for solving the tasks of durability of articles. The basic point of the developed methods intended for investigating the moisture-caused deformations is investigation of the groups of specimens by measuring deformations in the environment of fixed sorption moisture using four models. According to the methods described in this article, the dependence of deformations (eu) of various construction materials (concrete, porous concrete, sand-lime and ceramic bricks, cement-lime plasters) upon moisture and changes therein was investigated: eu = f(u). Analysing the materials with different capillary structures enables us to provide – in a very concise form – some References concerning value and nature of deformations. Linear moisture-caused deformations of basic construction materials (concrete, sand-lime and ceramic bricks, cement-lime plasters, porous concrete) vary within the limits of 0,33–0,77 mm/m. In case of articles containing organic fillings they can reach up to 6 mm/m. When the material is of a fine capillary structure the highest relative moisture elongation K of a material is observed in the environment of vapour area. Relative moisture elongation of the tested materials with the outset of intense capillary condensation varies from 0,05 mm/(mx%) to 0,51 mm/(mx%). First Published Online: 26 Jul 2012